2014
DOI: 10.1115/1.4028315
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Accurate Evaluation of Cooling in Data Centers

Abstract: Cooling is a major component in the enormous energy consumption in data centers. Accurate evaluation of cooling inside a data center forms the backbone of all the attempts for improving cooling efficiency. Models based on computational fluid dynamics (CFD) are typically used for accurate evaluation, but have a drawback of high computation time. This paper presents a novel thermal predictor to evaluate data center cooling in seconds. The key idea is to extract information from a single instance of CFD simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…To overcome the drawbacks of CFD, some dynamic models for fast estimation of the thermal environment in a data center have been developed. In [7], [8], it was found that for a fixed velocity field, temperature fields generated by multiple different boundary conditions can be superposed linearly. With this feature, the temperature field under real circumstances can be directly calculated by the superposition of a set of precalculated elementary processes.…”
Section: A Related Work 1) Estimation and Optimized Controlmentioning
confidence: 99%
“…To overcome the drawbacks of CFD, some dynamic models for fast estimation of the thermal environment in a data center have been developed. In [7], [8], it was found that for a fixed velocity field, temperature fields generated by multiple different boundary conditions can be superposed linearly. With this feature, the temperature field under real circumstances can be directly calculated by the superposition of a set of precalculated elementary processes.…”
Section: A Related Work 1) Estimation and Optimized Controlmentioning
confidence: 99%
“…The airflow within the data center causes heat generated from nodes to propagate to other nearby nodes, thereby increasing the inflow temperature of those nodes. Using the notion of thermal influence indices [38] that were derived using computational fluid dynamics simulations, we can calculate the steadystate temperatures at compute nodes and CRAC units in each data center. Because we assume the same physical layout for each of the data centers ( Figure 3.1), we use thermal influence indices derived for one data center layout based on an average workload that would be executed by the data center.…”
Section: Cooling Power Modelmentioning
confidence: 99%
“…5) Thermal Model: Using the notion of thermal influence indices [13] that were derived using computational fluid dynamics simulations, we can calculate the steady-state temperatures at compute nodes and CRAC units in each data center. Because we assume the same physical layout for each of the data centers ( Fig.…”
Section: System Model a Geo-distributed Levelmentioning
confidence: 99%